1992
DOI: 10.1105/tpc.4.5.597
|View full text |Cite
|
Sign up to set email alerts
|

A geminivirus replication protein is a sequence-specific DNA binding protein.

Abstract: The genome of the geminivirus tomato golden mosaic virus (TGMV) consists of two circular DNA molecules designated as components A and B. The A component encodes the only viral protein, AL1, that is required for viral replication. We showed that AL1 interacts specifically with TGMV A and B DNA by using an immunoprecipitation assay for AL1:DNA complex formation. In this assay, a monoclonal antibody against AL1 precipitated AL1:TGMV DNA complexes, whereas an unrelated antibody failed to precipitate the complexes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 50 publications
2
97
0
3
Order By: Relevance
“…In addition, the sequence ATTGGCTG at nt 1-8 in isolate C39 is followed by AATCGGTG at nt 44-51, AATGGGGG at nt 53-60 and the nearly complementary sequence TAACCCCC at nt 84-77. In other geminiviruses, nearly reiterated sequences of this kind interact with the AC1 gene product during viral DNA replication (Fontes et al, 1992 ;Argu$ ello-Astorga et al, 1994).…”
Section: Comparison Of Intergenic Regionsmentioning
confidence: 99%
“…In addition, the sequence ATTGGCTG at nt 1-8 in isolate C39 is followed by AATCGGTG at nt 44-51, AATGGGGG at nt 53-60 and the nearly complementary sequence TAACCCCC at nt 84-77. In other geminiviruses, nearly reiterated sequences of this kind interact with the AC1 gene product during viral DNA replication (Fontes et al, 1992 ;Argu$ ello-Astorga et al, 1994).…”
Section: Comparison Of Intergenic Regionsmentioning
confidence: 99%
“…Replication of DNA-A and DNA-B components relies on an interaction between the DNA-A-encoded replicationassociated protein (Rep) and reiterated motifs (termed iterons) located within the origin of replication (Argüello-Astorga et al, 1994;Fontes et al, 1992Fontes et al, , 1994Laufs et al, 1995;Gladfelter et al, 1997), which usually limits Rep trans-replication to its own DNA-A and DNA-B components. In contrast, the ability of intact and defective DNA-b satellites to be trans-replicated by distinct begomoviruses (Dry et al, 1997;Saunders et al, 2002;Mansoor et al, 2003) indicates that productive origin recognition is more relaxed for the satellite.…”
Section: Introductionmentioning
confidence: 99%
“…The product of gene AC1 is the only virus-encoded protein essential for ACMV DNA replication (Etessami et al, 1991). The protein from the related virus tomato golden mosaic virus (TGMV) binds in vitro to TGMV sequences located upstream of the stem-loop, but not to the stem-loop itself (Fontes et al, 1992). However, the analysis of TGMV and squash leaf curl virus (SqLCV) recombinants containing chimeric common region sequences has demonstrated that the stem loop structure is also an integral part of the replication origin (Lazarowitz et al, 1992).…”
mentioning
confidence: 99%